Strong and frequent T‐cell responses to the minor allergen Phl p 12 in Spanish patients IgE‐sensitized to Profilins. Issue 5 (19th December 2017) - Lund, G.; Brand, S.; Ramos, T.; Jimeno, L.; Boissy, P.; Vega, F.; Arina, M.; Christensen, L. H.; Hoof, I.; Meno, K. H.; Barber, D.; Blanco, C.; et al.
Abstract: Background: Profilins are dominant pan‐allergens known to cause cross‐sensitization, leading to clinical symptoms such as pollen‐food syndrome. This study aimed to determine the T‐cell response to Phl p 12 in profilin‐sensitized patients, by measuring the prevalence, strength and cross‐reactivity to clinically relevant profilins. Methods: The release of Phl p allergens from pollen was determined by mass spectrometry and immunochemistry. T‐cell responses, epitope mapping and cross‐reactivity to profilins (Phl p 12, Ole e 2, Bet v 2 and Mal d 4) were measured in vitro using PBMCs from 26 Spanish grass‐allergic donors IgE‐sensitized to profilin. Cross‐reactivity was addressed in vivo using 2 different mouse strains (BALB/c and C3H). Results: Phl p 12 and Phl p 1 are released from pollen simultaneously and in similar amounts. Both T‐cell response frequency (17/26 donors) and strength were comparable between Phl p 12 and Phl p 1. T‐cell cross‐reactivity to other profilins correlated with overall sequence homology, and 2 immunodominant epitope regions of Phl p 12 were identified. Data from mice immunized with Phl p 12 showed that cross‐reactivity to Bet v 2 was mediated by conserved epitopes and further influenced by additional genetic factors, likely to be MHC II. Conclusion: The strength, prevalence and cross‐reactivity of T‐cell responses towards Phl p 12 are comparable to the major allergen Phl p 1, which supports the hypothesis that T cells to Phl p 12 can play an important role in development of allergic symptoms, such as those associated with pollen‐food syndrome.